Extended main phase of some sudden commencement great geomagnetic storms with double SSCs - Srivastava, B.J.; Abbas, Habiba; Rao, D.R.K.; Pathan, B.M. (My University, 1999)
Hourly equatorial Dst (H) values for a few sudden commencement great geomagnetic storms recorded during the solar cycle 22 are plotted for 72 h of storm time and critically examined. Magnetic records taken at selected low latitude Indian stations are also scrutinised for finer details like SSCs, SIs and other fluctuations. Unusually prolonged main phases lasting more than 20 h characterize the two great storms of 13 March 1989 and 24 March 1991. A second SSC/SI pair, occurring some hours after the first main SSC, has also been identified in these storms. Only the great storm of 28 October 1991, with two SSCs and a main phase duration of 21 h, could be studied in conjunction with simultaneous interplanetary data, including Bz changes. Double negative Bz changes correlate well with the extended and enhanced main phase of this storm. Successive magnetic clouds preceded by interplanetary shock waves could generate such great magnetic storms in association with southward IMF changes.
Keywords: Geomagnetic storms; Indian stations; Magnetic records; Sudden storm commencement; Interplanetary shock waves